INVESTIGATING THE INTENTIONAL APPROACH OF CUSTOMERS TO USE THE ISLAMIC BANKING IN PAKISTAN: AN EMPIRICAL STUDY - Chandio, Abdul Rahim; Brohi, Moula Bux (Faculty of Islamic Economics and Business, Sultan Aji Muhammad Idris State Islamic University of Samarinda, 2024)
Abstract This study aims to investigate the perception of Islamic Banking users and measure the proposed behavioral factors like perceived usefulness, perceived ease of use, social influence, and attitude with the intention to use. This research inculcates the theory of planned behavior (TPB), unified theory of acceptance and use of technology (UTAUT), and technology acceptance model (TAM) in a perspective of Islamic Banking. The nature of the research is based on the quantitative methodology and follows the survey questionnaire in order to collect the data within the province of Sindh. For the data analysis 268 survey items were distributed among the Bank customers and the only 193 respondents materialized their feedback. For the testing the hypothesis SPSS version 24 was used. The results of the study show that all proposed constructs fond the positive and significant relationship with the criterion variable. Moreover, theoretical and practical significance of this study is related to behavior of consumer in Islamic Banking and it ensures the services and products via adoption, promotion, and propagation of Islamic banking as a social norm in Pakistan.